Das infâncias naturalistas à infância histórica: um estudo à luz da crítica de L. S. Vigotski à psicologia infantil - Santos, Priscilla Menescal Vieira dos (2019)
In general, childhood has been traditionally understood by psychology as an unquestionable, universal and natural fact, a stage of development. Recent academic researches show frequently two main definitions of childhood: a natural-biological stage and a socio-historical development – in which we define childhood as a biological stage, termed as a naturalistic childhood, according to LS Vygotsky's critique of naturalism in child psychology. However, these definitions have also proved to be mere thoughtless repetitions, in which we do not know what it means to affirm that childhood is a biological stage or even a socio-historical development. In the present work we opted for the use of childhood conceptions because it is, according to the definition of Santos (1996), an abstraction of individual properties defined by the values of culture. Thus, we draw on L. S. Vygotsky’s historical-cultural theory and his concept of culture to address childhood conceptions in two respects: 1) human beings as producers of culture and lifestyles, including childhood lifestyles; 2) society and culture as components of the true source of the child's individual development. Our question was formulated as follows: is it possible to verify in current productions the main characteristics, theoretical and epistemological bases of childhood’s conceptions that emerged with the institutionalization of Psychology? Therefore, the general objective of this work was to investigate how childhood conceptions, especially naturalistic conceptions, were related to Psychology at the moment of its constitution as a scientific discipline. The specific objectives were: 1) to identify how the different conceptions of childhood were constituted in modernity’s history; 2) construct an instrument for identification and analysis of childhood conceptions based on the text El problema de la edad (Vigotski, [1932] 2006); 3) to analyse doctoral researches in psychology that has as object of study childhood, child and / or child development, published between the years 2010 and 2016, aiming to verify what were the conceptions of childhood adopted. We identified close relationships between the epistemological and methodological problems of psychological discipline and the conceptions of childhood that emerged in its founding moments. Naturalistic childhoods are, in addition to other identified characteristics, conceptions with close alliances with natural sciences and have a strong ideological imprint. With the systematization of Vygotsky's critique of psychological science and child psychology we built an instrument capable of identifying and analysing childhood conceptions in psychology researches. In our analyses we found naturalistic conceptions of childhood in recent productions, based mainly on Piaget's theories; Freud and Jung. Also, we found the historical conception of childhood in three of the nine doctoral researches analysed, based on the psychological theories of Erik Erikson and Urie Bronfenbrenner.